Modern Midrash: the biblical canon and modern literature - Shaḳed, Gershon (AJS review, 2004)
Canonization of the Bible resulted from a consensus of those to whom it was addressed and a ruling group of religious elites that established its sanctity. They declared that “Torah was given to Moses at Sinai” and valued it above and beyond its literary value. The process of canonization was not a simple one. Several books were included only after struggles among various pressure groups. For example: “At first, Proverbs, Song of Songs and Ecclesiastes were considered non-canonical because they consisted of parables, but later the men of the Great Assembly interpreted them.” (ءAvot dءRabbi Natan, 1). Further: “The sages wished to exclude Ecclesiastes because it contained inconsistencies, but they included it because it begins and ends with teachings of Torah” (Shabbat, 30:b).